'I'd like to know why': Cultural capital and MA in Education students' interpretation of feedback commentaries - Mirador, Josephine F. (Animo Repository, 2014)
This article discusses the results of an investigation into selected MA in Education students' interpretation of feedback to their written assignments in a teaching and learning institution in the UK, using the framework of cultural capital and acculturation. A case study method was adopted to investigate four participants' thoughts and experiences with feedback over a period of two semesters. Participants were asked to go through a think-aloud process while responding to feedback from tutors to their assignments. Results of the think-aloud were used as springboard for interviews conducted with students. The article argues that students' diverse and variable interpretations of tutor feedback can be explained by Bourdieu's notion of 'connaissance' or knowledge as cultural capital. Additionally, students were found to have subscribed to the 'acculturation' process modelled by tutors in feedback provision. © 2013 Taylor & Francis.